2014
DOI: 10.1007/s00420-014-0934-9
|View full text |Cite
|
Sign up to set email alerts
|

Shift work, long working hours and preterm birth: a systematic review and meta-analysis

Abstract: Although in many of the included studies a positive association between long working hours and PTB was seen this did reach only marginal statistical significance. In the studies included in this review, working in shifts or in night shifts during pregnancy was not significantly associated with an increased risk for PTB. For both risk factors, due to the lack of high-quality studies focusing on the risks per trimester, in particular the third trimester, a firm conclusion about an association cannot be stated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…Epidemiological studies show small increases in miscarriage (Zhu et al 2004a;Bonde et al 2013;Stocker et al 2014), preterm birth (Mozurkewich et al 2000;Bonzini et al 2011) and intrauterine growth restriction (Croteau et al 2006;Abeysena et al 2009) in women who report carrying out shift work during pregnancy, whereas other studies show no associations (Zhu et al 2004b; van Melick et al 2014;Strohmaier et al 2018). These effects may be underestimated as a result of the various types and frequencies of shift work undertaken, as well as the variable behavioural responses to identical schedules (Gamble et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies show small increases in miscarriage (Zhu et al 2004a;Bonde et al 2013;Stocker et al 2014), preterm birth (Mozurkewich et al 2000;Bonzini et al 2011) and intrauterine growth restriction (Croteau et al 2006;Abeysena et al 2009) in women who report carrying out shift work during pregnancy, whereas other studies show no associations (Zhu et al 2004b; van Melick et al 2014;Strohmaier et al 2018). These effects may be underestimated as a result of the various types and frequencies of shift work undertaken, as well as the variable behavioural responses to identical schedules (Gamble et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…; van Melick et al . ), assessing the impact of shift work on pregnancy outcomes via epidemiological studies is difficult as a result of confounding factors and variable shift work schedules and types. Furthermore, effects of shift work on pregnancy outcomes cannot be tested directly because it is not possible to randomize women to shift work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, systematic reviews have suggested that occupational PA such as trunk bend (>1 hour/day), prolonged standing (>4 hours/day), shifting work and heavy physical work, particularly in late pregnancy, may increase the risk of PTB1011121314. However, the associations of non-occupational PA, including leisure-time, domestic, and commuting PA, with the risk of PTB have not been systematically evaluated.…”
mentioning
confidence: 99%
“…In women with back pain, these restrictions may be necessary to avoid exacerbation. For women in extremely physically demanding jobs, a few studies show increased risk of miscarriage and low birth weight but not preterm birth 18 ; and the evidence is not consistent. 3 In addition to potential for adverse obstetric outcomes, activity restriction may be recommended in women with physically demanding jobs to prevent musculoskeletal injuries and falls associated with physiologic changes of pregnancy such as increased load, change to the center of gravity, and ligament laxity.…”
Section: Box 1 Evidence-based Lifting Restrictionsmentioning
confidence: 98%